5 - La gestion des rapatriés de Libye dans la commune de Tchintabaraden (Niger) : les défis de l’urgence et du durable - Mounkaïla, Harouna (Africa Development, 2021)
In 2011 the war in Libya caused the departure of hundreds of thousands of foreign citizens. Niger, which shares a border with Libya, recorded nearly 114.100 arrivals of people in its territory between February 2011 and July 2012, including 6,278 foreigners according to official statistics. This massive population influx occurred in Niger within a political context marked by military transition, following the military overturn of 18 February 2010, as the country was simultaneously facing a food crisis for the second consecutive year. These factors have opened the debate about the social, economic and security implications of this reverse migration. For many observers these arrivals have brought significant shortfall to many households as they now have more mouths to. It is believed that this might worsen the food crisis and increasing insecurity in the country. Based on results of a research conducted in 2011 among the returnees in Tchintabaraden township, this article highlights the impact of the migrant influx.